Macau Between Republics:: Neither War nor Peace (1914-1918) - Cunha,Luís (2017)
During World War I, the Portuguese far-eastern colony of Macau underwent an intensification of the climate of instability that had hitherto characterized its life. Portugal and China, young republics both, projected their internal convulsions into their foreign policy. The two nations also nurtured an old dispute concerning the territorial delimitation of Macau. Dependent for its protection on Portugals traditional ally, Great Britain, via Hong Kong, the Portuguese colony survived thanks to a precarious modus vivendi with the Chinese. Portugal exercised in Macau a limited sovereignty, threatened continuously by the nationalist impetus of China. The risk of a Chinese military offensive against Macau never ceased. Although sheltered from the world conflict, Macau went through a time of great tension from 1914 to 1918.